Evaluation of urea-nitrate supplement made with Maillard reaction for delaying ruminal ammonia formation - Kurniawan Dedy Nanda; Apriani Vita; Yanza Yulianri Rizki; Nahrowi; Jayanegara Anuraga (BIO Web of Conferences)
Ruminants have a stomach that can convert NPN compounds as amino acids. This ability has not been effectively utilised. The present study aimed to determine the influence of urea-nitrate supplementation on rumen fermentation profiles in vitro. The urea-nitrate was prepared by employing the Maillard reaction (MR) using two different sugar sources, i.e., molasses and liquid waste of palm juice. The present study's randomized complete block design consisted of five treatments and four replications. The treatments are T0 = control diet; T1 = T0 + urea; T2 = T0 + urea-nitrate; T3 = T0 + urea-nitrate MR with molasses; T4 = T0 + urea-nitrate MR with liquid waste of palm juice, where urea and urea-nitrate supplementation treatments were expected to enhance dietary crude protein by 2% of the control diet. Results revealed that T3 treatments enhanced ammonia concentration up to 11.4% compared to T0, T1, and T4 (P<0.05). However, treatments were similar in terms of rumen pH, volatile fatty acids, microbial protein synthesis, total gas production, methane production, dry matter digestibility, and organic matter digestibility. In conclusion, the slow release urea-nitrate supplementation in ruminant feed may inhibits ammonia formation in the rumen in vitro.